Demistyfing consumer purchase intention for remanufactured auto parts / Loh Ka Chin...[et al.] - Loh, Ka Chin (Universiti Teknologi MARA, Kedah, 2019)
This study investigates customer purchase intention on remanufactured auto parts (RAPs) in the northern region of Malaysia. This study used an online survey of 158 respondents to identify factors of their knowledge of RAPs, how they perceive benefits, risk and price awareness, and the effects of their behavioral intentions. From this study, purchase intention was found to be significantly affected by all the mentioned factors in the market setting. Future research could further analyze green purchase intention by adding other perception variables such as perceived trust, self green identity and RAPs country of origin.